The effects of lactulose on constipation in patients with Parkinson's disease: An exploratory pilot study - Shin-ichiro Kubo; Mako Ito; Kyoko Matsuba; Tomohiro Shimono (eNeurologicalSci)
Introduction: Constipation is one of the most common non-motor symptoms of Parkinson's disease (PD) and is associated with reduced quality of life in patients with PD. The aim of this study was to evaluate the effect of lactulose on defecation status in patients with PD. Methods: In this open-label, single-center, exploratory pilot study, twenty-nine patients with PD received lactulose for three weeks for the treatment of constipation. The primary endpoint was the number of spontaneous bowel movements (SBMs). The secondary endpoints were stool consistency (Bristol Stool Form Scale [BSFS]) and the number of rescue laxatives used. Results: Twenty-five patients with PD completed the study. The number of SBMs recorded during the lactulose intervention period was significantly increased compared with that recorded during the pre-intervention period. During the intervention period, the BSFS scores of the patients increased significantly, whereas the number of rescue laxatives they used decreased significantly. No serious adverse events were observed during the study period. Lactulose was well-tolerated. Conclusions: The results of this study suggest that lactulose may be effective in improving defecation status in patients with PD. Further randomized controlled trials are needed to confirm the effects of lactulose on constipation in patients with PD.